The Adoption And Impact Of Human Resource Information Systems (HRIS) On Organizations In The Multimedia Super Corridor And Klang Valley In Malaysia - Wahome, Angela (2008)
This study examines the relationship between innovation and organization characteristics and the adoption of HRIS. In order to do this, innovation, organizational and environmental characteristics were studied, to find eight factors namely; relative advantage, complexity, compatibility, top management support, size, HRIS expertise, ownership and annual revenue.